2016
DOI: 10.18632/oncotarget.6973
|View full text |Cite
|
Sign up to set email alerts
|

TSGΔ154-1054 splice variant increases TSG101 oncogenicity by inhibiting its E3-ligase-mediated proteasomal degradation

Abstract: Tumor susceptibility gene 101 (TSG101) elicits an array of cellular functions, including promoting cytokinesis, cell cycle progression and proliferation, as well as facilitating endosomal trafficking and viral budding. TSG101 protein is highly and aberrantly expressed in various human cancers. Specifically, a TSG101 splicing variant missing nucleotides 154 to 1054 (TSGΔ154-1054), which is linked to progressive tumor-stage and metastasis, has puzzled investigators for more than a decade. TSG101-associated E3 li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…We conclude that the over-expression of TSG∆154-1054 prohibits the degradation of the full-length TSG101 protein, which is fully consistent with our recent discovery of the TSG∆154-1054 protein function as a competitive inhibitor of the ubiquitin-proteasome degradation of TSG101 protein [31].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…We conclude that the over-expression of TSG∆154-1054 prohibits the degradation of the full-length TSG101 protein, which is fully consistent with our recent discovery of the TSG∆154-1054 protein function as a competitive inhibitor of the ubiquitin-proteasome degradation of TSG101 protein [31].…”
Section: Resultssupporting
confidence: 90%
“…This discrepancy is likely attributable to the presence of TSG∆154-1054 in these cancer tissues. We previously demonstrated that the protein product of TSG∆154-1054 competitively binds to Tal, but not MDM2, thereby impeding the proper Tal binding to TSG101, leading to the protection of TSG101 from the subsequent polyubiquitination and following proteasomal degradation [31]. Our cycloheximide chase analysis indeed substantiated this TSG∆154-1054 triggered mechanism to protect the integrity of TSG101.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Using these two substrates, we discovered that the mRNA re-splicing event occurs on mature spliced mRNA, in which the normal splicing removes all authentic splice sites and brings the weak re-splice sites into close proximity [ 9 ]. The re-spliced TSG101 mRNA, TSG101Δ154-1054 mRNA ( Figure 1 a), produces an aberrant protein product that up-regulates the full-size TSG101 by interfering with the ubiquitin-dependent degradation of TSG101 protein [ 10 ]. Importantly, overexpression of the TSG101 protein enhances cell proliferation and promotes malignant tumor formation in nude mice [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%